WARM-UP EXERCISES AS A CRUCIAL FACTOR OF PREPARATION FOR PHYSICAL ACTIVITY: PHYSIOLOGICAL REASONING - Маракушин, Дмитро; Ісаєва, Інна; Кармазіна, Ірина; Хромко, Євгенія (SWorldJournal, 2024)
Physical activity can be challenging for the body, especially when performed suddenly and without proper preparation. To avoid the risk of injury and optimize a performance, athletes and trainers use warm-up exercises to prepare the body for activity. Pr